1999
DOI: 10.1063/1.370660
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermoelectric power factor in composite thermoelectrics

Abstract: The analytical properties of macroscopic transport coefficients of two-component composites are first used to discuss the thermoelectric power factor of such a composite. It is found that the macroscopic power factor can sometimes be greater than the power factors of both of the pure components, with the greatest enhancement always achieved in a parallel slabs microstructure with definite volume fractions for the two components. Some interesting examples of actual mixtures are then considered, where the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(86 citation statements)
references
References 12 publications
4
82
0
Order By: Relevance
“…This agrees sufficiently with calculations using a model by Bergman [9], which shows a maximum of the power factor S 2 σ (σ = electrical conductivity) at 33% ReSi 1.75 in ReSi 2.22 matrix.…”
Section: Resultssupporting
confidence: 91%
“…This agrees sufficiently with calculations using a model by Bergman [9], which shows a maximum of the power factor S 2 σ (σ = electrical conductivity) at 33% ReSi 1.75 in ReSi 2.22 matrix.…”
Section: Resultssupporting
confidence: 91%
“…40,41 This study demonstrates that the s and k of a composite can not be improved for high ZT, in comparison with that of either the best or worst thermoelectric parameter of the separate components of the composite, if the contribution from the phase interface/boundary is of little worth. 40,41 The thermoelectric properties calculated by them for the binary composite indicated that the ZT of the composite could never exceed the highest ZT of each separate component phase, although enhancement in the power factor could be achieved. The proof-of-principle of the EMA theory was demonstrated experimentally by Heremans et al 42 ,46-49 as the matrix phase deliver simultaneous improvement in the power factor and reduction in k leading to an increased ZT.…”
Section: -39mentioning
confidence: 87%
“…However, as shown theoretically by Bergman and Fel 14 and experimentally by Heremans and Jaworski, 15 it may be possible to enhance the power factor if the components are a ''high-quality thermoelectric'' and a ''benign metal.'' This paper is an extension of our earlier work [16][17][18] to systematically investigate the crystal growth, microstructure, composition and doping, and thermoelectric properties of the Mg 2 X compounds.…”
Section: Introductionmentioning
confidence: 97%